Grieg As Storyteller: The Poetics of the Ballade in G Minor, Op. 24. Issue 4 (10th April 2020) - Martin, Gregory
Abstract: Critical discussion of Edvard Grieg's Ballade has tended to dwell on more superficial aspects of its formal layout, rather than investigate the unique poetics that underlies its trajectory. This essay contends that in 1875, when he chose to write a song 'so people will see / that even the North can be beautiful', Grieg turned to the most profound and personal of Norway's literary inheritances, the sagas and Eddas, for formal, structural, and aesthetic inspiration. The juxtaposition of ancient folksong and late-Romantic harmony fuels a dynamic interaction that not only creates the effect of a great abyss of time, but also serves as the dramatic impetus for Grieg's narrative, one that gradually purges the theme of its chromaticism and transforms it into a barbaric final dance. Grieg's engagement with his material may be seen as something analogous to the oral poet, illuminating aspects of storytelling sometimes unfamiliar in the Western tradition.